Creating and Expanding the European Network Education and Training in Occupational Safety and Health (ENETOSH) to Build Capacity in OSH and Education - Bollmann, Ulrike; Moyo, Dingani; Policarpo, Diana de Sousa; Figueiredo, Vinka Longin Peš, Ilda Luísa; Dethleff, Claus; Tregenza, Timothy David (Taylor and Francis Group, 2022)
This group was created to bridge the gap between occupational safety and health experts and education experts. The most challenging aspects of starting and running the European Network Education and Training in Occupational Safety and Health (ENETOSH) have been the long underestimated role of education in the OSH policy area and, conversely, occupational safety and health as an unknown variable in the policy area of education. But the key to success has been in demonstrating mutual benefit: the contribution of safety and health to pedagogical quality and the contribution of education and training to the development of a culture of prevention. The chapter describes the outcome of 20 years of networking and the requirements on safety and health competence in a changing world of work and learning.